Optimal power allocation for NOMA-enabled D2D communication with imperfect SIC decoding - Yu, Shanshan; Khan, Wali Ullah; Zhang, Xiaoqing; Liu, Ju (Physical communication, 2021)
The combination of device-to-device (D2D) communication with non-orthogonal multiple access (NOMA) is an efficient solution to enhance the spectral efficiency and connection density of beyond fifth-generation cellular networks. In the paper, we optimize the power allocation of NOMA-enabled D2D communication. In particular, we formulate sum data rate maximization problem subject to the quality of services of cellular user and transmit power of D2D communication. To obtain the efficient solution, we exploit dual theory by using sub-gradient method to solve the dual variables. To gauge the performance of the proposed optimal power allocation scheme, the results are also compared with average power allocation schemes and orthogonal multiple access schemes. The simulation results unveil that the proposed optimization scheme significantly improve the data rate of D2D communication compared to the benchmark schemes.